2022
DOI: 10.1101/2022.11.16.22282416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Clinical Utility of the BMD-related comprehensive Genome-wide polygenic score in identifying individuals with a high risk of osteoporotic fractures

Abstract: Purpose: This study sought to construct genome-wide polygenic scores for femoral neck and total body BMD and to estimate their potential in identifying individuals with a high risk of osteoporotic fractures. Methods: Genome-wide polygenic scores were developed and validated for femoral neck and total body BMD. We externally tested the PGSs, both by themselves and in combination with available clinical risk factors, in 455,663 European ancestry individuals from the UK Biobank. The predictive accuracy of the dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 47 publications
(49 reference statements)
0
6
1
Order By: Relevance
“…Implementing individual-level genome-wide PGSs summarizing the underlying genetic predisposition of certain diseases in the clinical setting holds excellent promise. Previously, we developed and internally validated two genome-wide BMD-related PGSs using data from the UKB cohort [ 17 ]. Our findings indicated that both PGSs were significantly associated with incident fractures, even after being adjusted for FRAX clinical risk factors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Implementing individual-level genome-wide PGSs summarizing the underlying genetic predisposition of certain diseases in the clinical setting holds excellent promise. Previously, we developed and internally validated two genome-wide BMD-related PGSs using data from the UKB cohort [ 17 ]. Our findings indicated that both PGSs were significantly associated with incident fractures, even after being adjusted for FRAX clinical risk factors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we developed and internally validated two genome-wide BMD-related PGSs using data from the UKB cohort [ 17 ]. Our findings indicated that both PGSs were significantly associated with incident fractures, even after being adjusted for FRAX clinical risk factors [ 17 ]. In the current study, we replicated the two BMD-associated PGSs from previous work [ 17 ] and additionally derived a third PGS—metaPGS combining the effect of the two established PGSs and evaluated their predictive effect in an independent WHI postmenopausal women sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations